PENGARUH PENEMPATAN ISOCENTER TERHADAP KUALITAS CITRA DAN INFORMASI CITRA ANATOMI MRI BRAIN T1 FAST SPIN ECHO POTONGAN SAGITAL DI NASION DAN GLABELLA - Jackwin Surya. D. B; Sigit Wijokongko; Nanang Sulaksono (Perhimpunan Radiografer Indonesia (PARI), 2019)
Background : Before conducting an MRI examination, there will be a positioning. One of the positions carried out is the placement of isocenter. Isocenter is a magnetic center point where each gradient will be centered at that midpoint (Brown and Semelka, 2010). Different isocenter placements can affect image quality (Caramanos et al, 2010). In practical experience in the Telogorejo Semarang SMC Hospital, the placement of the isocenter in the nation while in Dr. Soetomo and Premier Surabaya Hospital placed Isocenter in Glabella. To examine the effect of isocenter placement on image quality and MRI brain T1 fast spin echo anatomical image information in the nasion and glabella and determine the optimal isocenter placement between the nasion and glabella. Method : This type of research is quantitative with an experimental approach. This research was conducted at Telogorejo SMC Hospital Semarang. Data in the form of 16 MRI images of sagittal brain pieces of T1 Fast Spin Echo weighting on isocenter placement in the nasion and glabella of 8 volunteers. Testing is done using the SPSS program where the image quality is analyzed by linear regression test, while for anatomical image information is analyzed by the Wilcoxon test. Result : The results of this study indicate that there is an effect of isocenter placement on the quality of MRI brain images of T1 fast spin echo sagittal pieces as seen from p value SNR (0.039) and CNR (0.010) <0.05 and from SNR percentage effect of 16.85% while CNR of 5, 8%. in addition to the influence, there are also differences in the anatomical image information of the MRI brain T1 fast spin echo sagittal section which is seen from the p value generated is 0.001 <0.05. Conclusion : Judging from the mean rank per anatomy, isocenter placement in the nasion is optimal in providing information on the mesencephalon, medulla oblongata, and cerebral subarachnoid space.